* Ethical and Islamic Perspectives of Biotechnology Research and Human Consumption of Genetically Modified Organisms - ABDUL HASEEB ANSARI; PARVEEN JAMAL (Hamdard Islamicus, 2021)
In order to ensure continued food supply to ever-growing populations, especially in developing and least developed countries, enough production of genetically modified (GM) agricultural produce is sine qua non. It is for this reason that agricultural biotechnology has been given priority and is getting all kinds of support from the governments of developed and developing countries. But almost all living modified organisms (LMOs) and GM foods have their origin in Western countries, especially from multinational companies, significantly Monsanto of the United States. These companies though are marketing their GM products both at national and international levels without giving due consideration to their safety aspects, especially to human consumption. Most of the biotech companies and scientists around the world, engaged with producing genetically modified organisms (GMOs), living and their use as non-living, are motivated either by short-term monetary gains or to earn fame. Some of their errant researches are tainted with violation of ethics pertaining to science and technology. In order to ensure the safety to human, animal or plant life or health there are two international legal instruments supported with local laws made thereunder. Both of them resort to application of precautionary principle but to serve different purposes. But the zeal to promote international trade has dominated the conservation of the biodiversity imperatives. Although Islam requires for all edibles to be permissible (ÍalÉl) and good for human consumption (Ïayyib), accentuated in form of the precautionary principle – which, enshrined in several international and national legal instruments, has to be observed by producing and importing countries and which has to be environmentally friendly – but producing countries do not ensure the safety of biotech food. The precautionary principle has further been strengthened by various SharÊ‘ah principles. This paper demonstrates the ethical and Islamic perspective of production and use of GMOs.